Imprint Information (ARTic, 2025)
Advisory Board Prof. Agnieszka ZIEMISZEWSKA / Polish-Japan Academy of Information Technology in Warsaw, Poland Prof. Arafat AL-NAIM / American University in the United Arab Emirates, UAE Prof. Dr. Ali Osman ALAKUŞ / Dicle University, Türkiye Prof. Christopher Scott / Iowa State University, USA Prof. Dr. Didem ÇATAL / Çanakkale Onsekiz Mart University, Türkiye Prof. Dr. Doğan ARSLAN / Medeniyet University, Türkiye Prof. Eric Olivares LIRA / IED University Barcelona, Spain Prof. Evripides ZANTIDES / Cyprus University of Technology, Cyprus Prof. Dr. Nil Yıldız DUBAN / Afyon Kocatepe University, Türkiye Prof. Rikke HANSEN / SDU Kolding, Denmark Prof. Yusuf KEŞ / Süleyman Demirel University, Türkiye Assoc. Prof. Dr. Çağrı GÜMÜŞ / KTO Karatay University, Türkiye Assoc. Orhun TÜRKER / Bolu Abant İzzet Baysal University, Türkiye Assoc. Prof. Shahid Adeel / Government  College University, Pakistan Assist. Prof. Dr. Fatih YILMAZ/ Dicle University, Türkiye Assist. Prof. Dr. Orhan SEVİNDİK / Istanbul University – Cerrahpaşa, Türkiye Lecturer Daniel MEIER/ DIPLOMA University, Germany Res. Assist. Dilara AYTEKİN / Anadolu University, Türkiye Scientific Board Prof. Dr. Abdulgani Arıkan, Selçuk University, Türkiye Prof. Dr. Adnan Sözen, Gazi University, Türkiye Prof. Dr. Adnan Tepecik, Başkent University, Türkiye Prof. Dr. Andreas Berchtold, Munich University of Applied Sciences, Germany Prof. Dr. Agnieszka Ziemiszewska, Polish-Japanese Academy of Information Technology, Poland Prof. Dr. Alexandra Pekarovicova, Western Michigan University, United States Prof. Dr. Ali Atıf Polat, Selçuk University, Türkiye Prof. Dr. Anna Tzolovska, Sofia University, Bulgaria Prof. Dr. Antoinette J. Muntjewerff, University of Amsterdam, Netherlands Prof. Dr. Arafat Al-Naim, American University in the Emirates, United Arab Emirates Prof. Dr. Arif Özcan, Marmara University, Türkiye Prof. Dr. Arvind Singhal, University of Texas, United States Prof. Dr. Ata Yakup Kaptan, Ondokuz Mayıs University, Türkiye Prof. Dr. Atilla Döl, Niğde University, Türkiye Prof. Dr. Ayşe Derya Kahraman, Istanbul University-Cerrahpaşa, Türkiye Prof. Dr. Azize Melek Önder, Necmettin Erbakan University, Türkiye Prof. Dr. Björn Kruselin, Köping University, Sweden Prof. Dr. Byoung-Il Sunnam, Seoul University, South Korea Prof. Dr. Candan Dedelioğlu, Yalova University, Türkiye Prof. Dr. Cem Aydemir, Marmara University, Türkiye Prof. Dr. Christopher Scott, Iowa State University, United States Prof. Dr. Colleen Sexton, Governors State University, United States Prof. Dr. Csaba Horvath, Óbuda University, Hungary Prof. Dr. Çağrı Gümüş, KTO Karatay University, Türkiye Prof. Dr. David Gethin, Swansea University, United Kingdom Prof. Dr. Davide Deganello, Swansea University, United Kingdom Prof. Dr. Detlef Hartman, Stuttgart Media University, Germany Prof. Dr. Didem Çatal, Çanakkale Onsekiz Mart University, Türkiye Prof. Dr. Doğan Arslan, Medeniyet University, Türkiye Prof. Dr. Don M. Flouroy, Ohio University, United States Prof. Dr. Dorian Leljak, Royal College of Music, United Kingdom Prof. Dr. Douglas Bousfield, University of Maine, United States Prof. Dr. Douglas Franklin, Ohio University, United States Prof. Dr. Dragoljub Novaković, University of Novi Sad, Serbia Prof. Dr. Efe N. Gençoğlu, Marmara University, Türkiye Prof. Dr. Elena Fedorovskaya, Rochester Institute of Technology, United States Prof. Dr. Emet Egemen Aslan, Selçuk University, Türkiye Prof. Dr. Emre İkizler, Marmara University, Türkiye Prof. Dr. Erdoğan Köse, Istanbul University-Cerrahpaşa, Türkiye Prof. Dr. Euripides Zontides, Cyprus University of Technology, Cyprus Prof. Dr. Evgeny Bablyuk, Moscow Polytechnic University, Russia Prof. Dr. Evren Bilge Kutlay, Istanbul Sabahattin Zaim University, Türkiye Prof. Dr. Evren Karayel Gökkaya, Çanakkale Onsekiz Mart University, Türkiye Prof. Dr. Evren Karayel Gökkuşağı, Çanakkale Onsekiz Mart University, Türkiye Prof. Dr. Fatih Başbuğ, Akdeniz University, Türkiye Prof. Dr. Fatih Özkafa, Marmara University, Türkiye Prof. Dr. Feng-Chiao Chung, National Pingtung University, Taiwan Prof. Dr. Fritz Bircherhaute, School of Engineering and Architecture of Fribourg, Switzerland Prof. Dr. Gökhan Aybulus, Anadolu University, Türkiye Prof. Dr. Gunter Hübnerhoch, University of Media, Germany Prof. Dr. Güler Akalan, Gazi University, Türkiye Prof. Dr. Gwo-Dong Chen, National Central University, Taiwan Prof. Dr. Hafize Melek Hidayetoğlu, Selçuk University, Türkiye Prof. Dr. Hani Ezeldinaljouf, University, Saudi Arabia Prof. Dr. Harun Hilmi Polat, Selçuk University, Türkiye Prof. Dr. He Huan, Minjiang University, Bosnia and Herzegovina Prof. Dr. Henry Giera, Munich University of Applied Sciences, Germany Prof. Dr. Hüseyin Elmas, Gazi University, Türkiye Prof. Dr. Irwan Harnoko, Pradita University, Indonesia Prof. Dr. İnan Güler, Gazi University, Türkiye Prof. Dr. İsa Eliri, Kırıkkale University, Türkiye Prof. Dr. J. Ana Donaldson, AECT Former President, United States Prof. Dr. J. Michael Specto, University of North Texas, United States Prof. Dr. Jerry Willis, Manhattanville College, United States Prof. Dr. Johannes Backhaus, University of Wuppertal, Germany Prof. Dr. Karl-Heinz Selbmann, Bern University of Applied Sciences, Germany Prof. Dr. Kye-Soo Myung, Konkuk University, South Korea Prof. Dr. Lale Altınkurt, Muğla Sıtkı Koçman University, Türkiye Prof. Dr. Laura Dimitrova, Sofia University, Bulgaria Prof. Dr. Laurens Patzlaff, Lübeck University of Music, Germany Prof. Dr. Levent Mercin, Kütahya Dumlupınar University, Türkiye Prof. Dr. Li Xu, Beijing Institute of Graphic Communication, China Prof. Dr. Lutz Engisch, Munich University of Applied Sciences, Germany Prof. Dr. Lütfi Hidayetoğlu, Selçuk University, Türkiye Prof. Dr. Lütfü Kaplanoğlu, Yıldız Technical University, Türkiye Prof. Dr. Malcolm Keif, California Polytechnic State University, United States Prof. Dr. Marina Stock McIsaac, Arizona State University, United States Prof. Dr. Martin Dreher, Stuttgart Media University, Germany Prof. Dr. Masafumi Ogawa, Yokohama National University, Japan Prof. Dr. Mehmet Oktav, Marmara University, Türkiye Prof. Dr. Mehmet Özkartal, Süleyman Demirel University, Türkiye Prof. Dr. Mei-Mei Chang, National Pingtung University, Taiwan Prof. Dr. Min Jou, National Taiwan Normal University, Taiwan Prof. Dr. Mustafa Cevat Atalay, Gaziantep University, Türkiye Prof. Dr. Mustafa Küçüköner, Necmettin Erbakan University, Türkiye Prof. Dr. Mutluhan Taş, Selçuk University, Türkiye Prof. Dr. Nabi Bux Jumani, International Islamic University, Pakistan Prof. Dr. Neslihan Kıyar, Kocaeli University, Türkiye Prof. Dr. Nil Yıldız Duban, Afyon Kocatepe University, Türkiye Prof. Dr. Nureddin Gülaçti, Kütahya Dumlupınar University, Türkiye Prof. Dr. Nurgül Kılınç, Selçuk University, Türkiye Prof. Dr. Pajamas Pachon Klare, Sukhothai Thammathirat Open University, Thailand Prof. Dr. Paul Dan Fleming, Western Michigan University, United States Prof. Dr. Peter Urban, University of Wuppertal, Germany Prof. Dr. Rahmi Aksungur, Mimar Sinan Fine Arts University, Türkiye Prof. Dr. Raif Kalyoncu, Karadeniz Technical University, Türkiye Prof. Dr. Robert G. Doyle, Associate Dean, Harvard University, United States Prof. Dr. Safa Yeprem, Marmara University, Türkiye Prof. Dr. Said Abubakr, Western Michigan University, United States Prof. Dr. Samya El Sherbin, Helwan University, Egypt Prof. Dr. Semiha Yenidoğan, Marmara University, Türkiye Prof. Dr. Serkan İlden, Kastamonu University, Türkiye Prof. Dr. Sharon Smaldino, Northern Illinois University, United States Prof. Dr. Shi Zengquan, Shandong University of Art and Design, China Prof. Dr. Sinan Sönmez, Marmara University, Türkiye Prof. Dr. Stefan Altakov, Sofia University, Bulgaria Prof. Dr. Stefan Aufenanger, University of Mainz, Germany Prof. Dr. Stefan Brües, University of Wuppertal, Germany Prof. Dr. Stephan Guttler, Stuttgart Media University, Germany Prof. Dr. Steve Harmon, Georgia Institute of Technology, United States Prof. Dr. Teresa Franklin, Ohio University, United States Prof. Dr. Tim Claypole, Swansea University, United Kingdom Prof. Dr. Tolga Akalın, Giresun University, Türkiye Prof. Dr. Türkün Şahinbaşkan, Marmara University, Türkiye Prof. Dr. Ulrike Herzau Gerhardt, Leipzig University, Germany Prof. Dr. Valker Jansen, Stuttgart Media University, Germany Prof. Dr. Wolfgang Kühn, University of Wuppertal, Germany Prof. Dr. Yeşim Zümrüt, Çanakkale Onsekiz Mart University, Türkiye Prof. Dr. Yung-Cheng Hsie, National Taiwan University, Taiwan Prof. Dr. Yusuf Keş, Süleyman Demirel University, Türkiye Prof. Dr. Zafer Kurtaslan, Ankara Music and Fine Arts University, Türkiye Prof. Dr. Zuhal Türktaş, Selçuk University, Türkiye  Assoc. Prof. Dr. Abdullah Cem Özal, Muğla Sıtkı Koçman University, Türkiye Assoc. Prof. Dr. Adem Yücel, Tokat Gaziosmanpaşa University, Türkiye Assoc. Prof. Dr. Ahmet Akgül, Marmara University, Türkiye Assoc. Prof. Dr. Ali Ertuğrul Küpeli, Gazi University, Türkiye Assoc. Prof. Dr. Aybige Demirci Şenkal, Ankara Music and Fine Arts University, Türkiye Assoc. Prof. Dr. Aydın Zor, Akdeniz University, Türkiye Assoc. Prof. Dr. Bahadır Uçan, Yıldız Technical University, Türkiye Assoc. Prof. Dr. Batuhan Kurt, Marmara University, Türkiye Assoc. Prof. Dr. Burak Erhan Tarlakazan, Kastamonu University, Türkiye Assoc. Prof. Dr. Cihan Şule Külük, Bolu Abant İzzet Baysal University, Türkiye Assoc. Prof. Dr. Dalida Karic-Hadziahmetovic, Academy of Fine Arts Sarajevo, Bosnia and Herzegovina Assoc. Prof. Dr. Doğan Tutak, Marmara University, Türkiye Assoc. Prof. Dr. Duygu Kahraman, Anadolu University, Türkiye Assoc. Prof. Dr. Elif Şenel, Ondokuz Mayıs University, Türkiye Assoc. Prof. Dr. Elif Tarlakazan, Kastamonu University, Türkiye Assoc. Prof. Dr. Emine Arman Kandırmaz, Marmara University, Türkiye Assoc. Prof. Dr. Eren Evin Kılıçkaya, Kütahya Dumlupınar University, Türkiye Assoc. Prof. Dr. Erol Murat Yıldız, Giresun University, Türkiye Assoc. Prof. Dr. Ertan Toy, Yıldız Technical University, Türkiye Assoc. Prof. Dr. Eylem Tataroğlu, Başkent University, Türkiye Assoc. Prof. Dr. Fahme Dabaj, Eastern Mediterranean University, Türkiye Assoc. Prof. Dr. Fethi Kaba, Anadolu University, Türkiye Assoc. Prof. Dr. Gülce Coşkun Şentürk, Muğla Sıtkı Koçman University, Türkiye Assoc. Prof. Dr. Hakan Alp, Istanbul University-Cerrahpaşa, Türkiye Assoc. Prof. Dr. Haldun Şekerci, Kütahya Dumlupınar University, Türkiye Assoc. Prof. Dr. Halide Okumuş, Çanakkale Onsekiz Mart University, Türkiye Assoc. Prof. Dr. Hami Onur Bingöl, Kütahya Dumlupınar University, Türkiye Assoc. Prof. Dr. Harun Diler, Akdeniz University, Türkiye Assoc. Prof. Dr. Hatice Harmankaya, Selçuk University, Türkiye Assoc. Prof. Dr. John I-Tsun Chiang, National Changhua University of Education, Taiwan Assoc. Prof. Dr. Kye-Soo Myung, Konkuk University, South Korea Assoc. Prof. Dr. Lale Altınkurt, Muğla Sıtkı Koçman University, Türkiye Assoc. Prof. Dr. Laura Dimitrova, Sofia University, Bulgaria Assoc. Prof. Dr. Laurens Patzlaff, Lübeck University of Music, Germany Assoc. Prof. Dr. Levent Mercin, Kütahya Dumlupınar University, Türkiye Assoc. Prof. Dr. Li Xu, Beijing Institute of Graphic Communication, China Assoc. Prof. Dr. Lutz Engisch, Munich University of Applied Sciences, Germany Assoc. Prof. Dr. Lütfi Hidayetoğlu, Selçuk University, Türkiye Assoc. Prof. Dr. Lütfü Kaplanoğlu, Yıldız Technical University, Türkiye Assoc. Prof. Dr. Malcolm Keif, California Polytechnic State University, United States Assoc. Prof. Dr. Mana Sezdi, Istanbul University-Cerrahpaşa, Türkiye Assoc. Prof. Dr. Marina Stock McIsaac, Arizona State University, United States Assoc. Prof. Dr. Martin Dreher, Stuttgart Media University, Germany Assoc. Prof. Dr. Masafumi Ogawa, Yokohama National University, Japan Assoc. Prof. Dr. Mehmet Ferruh Haşıloğlu, Atatürk University, Türkiye Assoc. Prof. Dr. Mehmet Oktav, Marmara University, Türkiye Assoc. Prof. Dr. Mehmet Özkartal, Süleyman Demirel University, Türkiye Assoc. Prof. Dr. Mehtap Bingöl, Ankara Hacı Bayram Veli University, Türkiye Assoc. Prof. Dr. Mei-Mei Chang, National Pingtung University, Taiwan Assoc. Prof. Dr. Menekşe Suzan Teker, Akdeniz University, Türkiye Assoc. Prof. Dr. Merve Yıldırım, Giresun University, Türkiye Assoc. Prof. Dr. Min Jou, National Taiwan Normal University, Taiwan Assoc. Prof. Dr. Mine Değirmenci Aydın, Ordu University, Türkiye Assoc. Prof. Dr. Mine Erdem Köroğlu, Selçuk University, Türkiye Assoc. Prof. Dr. Mustafa Cevat Atalay, Gaziantep University, Türkiye Assoc. Prof. Dr. Mustafa Kınık, Necmettin Erbakan University, Türkiye Assoc. Prof. Dr. Mustafa Küçüköner, Necmettin Erbakan University, Türkiye Assoc. Prof. Dr. Mutluhan Taş, Selçuk University, Türkiye Assoc. Prof. Dr. Murat Kara, Burdur Mehmet Akif Ersoy University, Türkiye Assoc. Prof. Dr. Nabi Bux Jumani, International Islamic University, Pakistan Assoc. Prof. Dr. Neslihan Kıyar, Kocaeli University, Türkiye Assoc. Prof. Dr. Nihat Sezer Sabahat, Ordu University, Türkiye Assoc. Prof. Dr. Nil Yıldız Duban, Afyon Kocatepe University, Türkiye Assoc. Prof. Dr. Nureddin Gülaçti, Kütahya Dumlupınar University, Türkiye Assoc. Prof. Dr. Nurgül Kılınç, Selçuk University, Türkiye Assoc. Prof. Dr. Oğuz Yurttadur, Selçuk University, Türkiye Assoc. Prof. Dr. Osman Çaydere, Gazi University, Türkiye Assoc. Prof. Dr. Osman Şimşeker, Marmara University, Türkiye Assoc. Prof. Dr. Oya Aşan Yüksel, Kütahya Dumlupınar University, Türkiye Assoc. Prof. Dr. Ömer Zaimoğlu, Akdeniz University, Türkiye Assoc. Prof. Dr. Özcan Özkarakoç, Akdeniz University, Türkiye Assoc. Prof. Dr. Pajamas Pachon Klare, Sukhothai Thammathirat Open University, Thailand Assoc. Prof. Dr. Paul Dan Fleming, Western Michigan University, United States Assoc. Prof. Dr. Peter Urban, University of Wuppertal, Germany Assoc. Prof. Dr. Pınar Toktaş, Ankara Hacı Bayram Veli University, Türkiye Assoc. Prof. Dr. Rahmi Aksungur, Mimar Sinan Fine Arts University, Türkiye Assoc. Prof. Dr. Raif Kalyoncu, Karadeniz Technical University, Türkiye Assoc. Prof. Dr. Rikke Hansen, Royal Danish Academy of Fine Arts, Denmark Assoc. Prof. Dr. Robert G. Doyle, Associate Dean, Harvard University, United States Assoc. Prof. Dr. Ruhi Konak, Kastamonu University, Türkiye Assoc. Prof. Dr. Safa Yeprem, Marmara University, Türkiye Assoc. Prof. Dr. Said Abubakr, Western Michigan University, United States Assoc. Prof. Dr. Samir Mirzayev, Akdeniz University, Türkiye Assoc. Prof. Dr. Samya El Sherbin, Helwan University, Egypt Assoc. Prof. Dr. Selçuk Ulutaş, Nevşehir Hacı Bektaş Veli University, Türkiye Assoc. Prof. Dr. Selda Güzel, Selçuk University, Türkiye Assoc. Prof. Dr. Selma Şahin, Kütahya Dumlupınar University, Türkiye Assoc. Prof. Dr. Semih Delil, Ankara Hacı Bayram Veli University, Türkiye Assoc. Prof. Dr. Semiha Yenidoğan, Marmara University, Türkiye Assoc. Prof. Dr. Serkan İlden, Kastamonu University, Türkiye Assoc. Prof. Dr. Sharon Smaldino, Northern Illinois University, United States Assoc. Prof. Dr. Shi Zengquan, Shandong University of Art and Design, China Assoc. Prof. Dr. Sinan Sönmez, Marmara University, Türkiye Assoc. Prof. Dr. Snezhina Biserova, Sofia University, Bulgaria Assoc. Prof. Dr. Stefan Altakov, Sofia University, Bulgaria Assoc. Prof. Dr. Stefan Aufenanger, University of Mainz, Germany Assoc. Prof. Dr. Stefan Brües, University of Wuppertal, Germany Assoc. Prof. Dr. Stephan Guttler, Stuttgart Media University, Germany Assoc. Prof. Dr. Steve Harmon, Georgia Institute of Technology, United States Assoc. Prof. Dr. Şerife Yıldız, Selçuk University, Türkiye Assoc. Prof. Dr. Teresa Franklin, Ohio University, United States Assoc. Prof. Dr. Tim Claypole, Swansea University, United Kingdom Assoc. Prof. Dr. Tolga Akalın, Giresun University, Türkiye Assoc. Prof. Dr. Tülay Gümüşer, Selçuk University, Türkiye Assoc. Prof. Dr. Türkün Şahinbaşkan, Marmara University, Türkiye Assoc. Prof. Dr. Uğur Günay Yavuz, Akdeniz University, Türkiye Assoc. Prof. Dr. Ulrike Herzau Gerhardt, Leipzig University, Germany Assoc. Prof. Dr. Valker Jansen, Stuttgart Media University, Germany Assoc. Prof. Dr. Wang Zhijun, Shanxi University, China Assoc. Prof. Dr. Wolfgang Kühn, University of Wuppertal, Germany Assoc. Prof. Dr. Wu Wenyu, Renmin University of China, China Assoc. Prof. Dr. Yeşim Zümrüt, Çanakkale Onsekiz Mart University, Türkiye Assoc. Prof. Dr. Yeşim Zümrüt, Çanakkale Onsekiz Mart University, Türkiye Assoc. Prof. Dr. Yung-Cheng Hsie, National Taiwan University, Taiwan Assoc. Prof. Dr. Yusuf Keş, Süleyman Demirel University, Türkiye Assoc. Prof. Dr. Zafer Kurtaslan, Ankara Music and Fine Arts University, Türkiye Assoc. Prof. Dr. Zafer Lehimler, Atatürk University, Türkiye Assoc. Prof. Dr. Zhenyu Lijian, Gannon University, United States Assoc. Prof. Dr. Zhi-Feng Liu, National Central University, Taiwan Assoc. Prof. Dr. Zhou Feng, China Academy of Art, China Assoc. Prof. Dr. Zuhal Türktaş, Selçuk University, Türkiye Dr. Farah Tahirova Vienna Cultural Society Austria Dr. Georgij Petriaszwili Warsaw University of Technology Poland Dr. Nora Wetzold Chemnitz University of Technology Germany Dr. Patrycja Longawa University of Information Technology and Management Rzeszow Poland Dr. Sasan Gooranlin Köping University Sweden Dr. Shahid Adeel Associate Professor Government College University Faisalabad Pakistan Dr. Uta Fugmann Chemnitz University of Technology Germany Lect. Ayten Adelpharos University In Alexandria Egypt Lect. Daniel Meier / DIPLOMA University, Germany Teacher Vesna Zidar Antlej Vız Os Rogatec Slovenia Music Scientific Committee Prof. Arman Artaç, Anadolu University State Conservatory Department of Performing Arts / Opera Major Prof. Hüseyin Bülent Akdeniz, Anadolu University State Conservatory Department of Music/Stringed Instruments Major Prof. Dr. Hanefi Özbek Uşak University Faculty of Medicine Dean, Istanbul Medipol University, Faculty of Fine Arts, Design and Architecture – Department of Music, Turkish Music Department Prof. Sancar Tunalı, Anadolu University State Conservatory Department of Performing Arts / Opera Major Prof. Volkan Gidiş, İstanbu Medipol University / Faculty of Fine Arts Design and Architecture / Department of Music / Turkish Music Assoc. Dilara Çelik, Anadolu University State Conservatory, Department of Performing Arts / Opera Major Assoc. Prof. Dr. Raşit Görkem Aytimur, Ankara University of Music and Fine Arts Faculty of Music and Performing Arts / Department of Voice Education Assoc. Prof. Ayşe Dağıstanlı Parlar, Hacettepe University Ankara State Conservatory Department of Performing Arts / Department of Opera Assist. Prof. Member Funda Yazıksız, Ankara University of Music and Fine Arts Faculty of Music and Performing Arts / Department of Voice Education Assist. Prof. Harun Keskin, Muğla Sıtkı Koçman University Department of Fine Arts Education / Music Education Department Assist. Prof. Dr. Özge Güncan, Anadolu University State Conservatory Department of Music / Department of Piano  Notice All texts in this special issue were presented as papers at the 3rd International Fine Arts, Printing, and Sustainability Congres. Copyrights The copyrights of the works published in the journal belong to the authors, and the works are licensed under Creative Commons Attribution NonCommercial 4.0 International (CC BY-NC 4.0).